2019
DOI: 10.1111/gcbb.12600
|View full text |Cite
|
Sign up to set email alerts
|

Sweetcane (Erianthus arundinaceus) as a native bioenergy crop with environmental remediation potential in southern China: A review

Abstract: Sweetcane (Erianthus arundinaceus [Retzius] Jeswiet) is an ecologically dominant warm‐season perennial grass native to southern China. It traditionally plays an important role in sugarcane breeding due to its excellent biological traits and genetic relatedness to sugarcane. Recent studies have shown that sweetcane has a great potential in bioenergy and environmental remediation. The objective of this paper is to review the current research on sweetcane biology, phenology, biogeography, agronomy, and conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…For instance, sweetcane biomass yield in test field reached to 43.76 t/ha in Huaihua, Hubei, while it gave 38 t/ha when tested at Changsha, Hunan. When tested at Nanning, Guangxi, the biomass yield was 11.27–25.16 t/ha while in constructed wetland, it produced 9.5 t/ha biomass (Hou et al., 2015; Wang et al., 2019; Yao et al., 2016; Zeng et al, 2013. A study on 20 sweetcane varieties cultivated in Sichuan Province showed that coefficient of dry matter production per plant was 25% (Liang, 2011).…”
Section: Biomass Resources Of Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, sweetcane biomass yield in test field reached to 43.76 t/ha in Huaihua, Hubei, while it gave 38 t/ha when tested at Changsha, Hunan. When tested at Nanning, Guangxi, the biomass yield was 11.27–25.16 t/ha while in constructed wetland, it produced 9.5 t/ha biomass (Hou et al., 2015; Wang et al., 2019; Yao et al., 2016; Zeng et al, 2013. A study on 20 sweetcane varieties cultivated in Sichuan Province showed that coefficient of dry matter production per plant was 25% (Liang, 2011).…”
Section: Biomass Resources Of Chinamentioning
confidence: 99%
“…It is considered an important genetic source for the sugarcane breeding programme. The species is related to taxa in Mi scanthus, Narenga, Saccharum and Sclerostachya, so it is considered a member of the 'sugarcane complex' (Amalraj & Balasundaram, 2006;Wang et al, 2019).All sweetcanes were found in the tropical and subtropical areas of China, specifically in the regions east of the Tibetan Plateau, south of Huai River-Qinling Mountains line. Sweetcane was generally found below an altitude of 1,500 m; however, it could be distributed up to 2,350 m (Yan et al, 2009).…”
mentioning
confidence: 99%
“…Prior reports have identified T. arundinaceum as a potential biomass and bioenergy feedstock (Dao et al, ; Palmer et al, ; Wang et al, ; Zhang et al, ), though cold hardiness is limited to USDA Zone 7b. The new interspecific Tripidium hybrids examined in this study demonstrated high biomass yields ranging from 24 to 61 dry Mg/ha for the third growing season within the temperate climes of Western North Carolina, USDA Zone 6b/7a (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Sugarcane wild relative E. arundinaceus is a potential donor for many genes related to biomass and tolerance to biotic and abiotic stresses 14 16 . Introgression of many genes from E. arundinaceus into sugarcane through conventional and biotechnological approaches has improved the agronomic performance of sugarcane varieties 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%